Answer :

L.H.S: tan θ + tan (90° - θ)

= tan θ + cot θ


[tan (90° - θ) = cot θ]







= sec θ cosec θ


= sec θ sec (90° - θ) [cosec θ = sec (90° - θ)]


: R.H.S


Hence, proved.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses